Implementation of PT Petrokimia Gresik's Corporate Social Responsibility "Kampung Sehat" to Improve The Quality of Life of The Community - Maulidiya, Nur Muadhimah; Kusumaningsih, Ambar (Jurnal Akuntansi, Manajemen dan Ilmu Ekonomi (Jasmien), 2024)
This research focuses on the implementation of PT Petrokimia Gresik's Corporate Social Responsibility (CSR) in the “Kampung Sehat” program in Tlogopojok Village. The research method was carried out using a qualitative approach with a case study method. Case study data was obtained through observation, interviews, and related documents. The research results show that the implementation of the “Kampung Sehat” CSR in Tlogopojok Village is realized with programs that focus on improving community health and environmental sustainability. Some of these programs include the Sekolah Kader Kampung Sehat, Jus Sehat, Bugar Academy, and Mas Darsa Community. PT Petrokimia Gresik strives to implement CSR to have a positive contribution in accordance with the triple bottom line (TBL) concept, aiming to balance the social, economic, and environmental aspects.